A method for improving the crack resistance of aluminum alloy aircraft skin inspired by plant leaf. (April 2020) - Wu, Lushen; Wang, Teng; Hu, Yun; Liu, Jiaming; Song, Minjie
Highlights: The method can effectively relieve stress concentration around the crack tip. The method achieves a good crack resistance performance comparing with other methods. The effects of bio-inspired structure are related to the shape of plastic zone. The method is predicted to retard crack growth in alluminum alloy. Abstract: Aircraft skins are likely to experience cracks and fracture failure due to the combined action of shear, bending, and torsional load. Inspired by the crack resistance exhibited by plant leaf, a method is proposed to improve the crack resistance of aluminum alloy aircraft skin. The characteristic parameters of main and secondary leaf veins are extracted by image edge detection and analysis methods. According to a constructed collection of self-similar fractal sets, a bio-inspired residual stress field with fractal characteristics extracted from leaf veins is applied to specimens ahead of crack tip by using laser peening. The effects of fractal parameters on crack retardation are analyzed using interaction integral. The results show that the stress intensity factor ahead of crack tip is reduced by applying a bio-inspired residual stress field, whereas the plastic zone area ahead of crack tip is enlarged. The correlation between these two trends reveals the mechanism of stress intensity decrease after the introduction of bio-inspired residual stress field. The optimal crack retardation effect is achieved at a fractal angle of 55°, at which the residual fatigue life is increased by up to 203.0%. Compared with square-shaped laser peening, full-coverage laser peening, square criss-cross pattern method, and single-edge notched tensile (SENT) specimen repair method, the proposed method achieves the longest residual fatigue life, which is almost three times that of the square-shaped laser peening method. Therefore, this theoretical study presents a potential method for improving the crack resistance of aluminum alloy aircraft skin.